Cytoskeletal network underlying the human erythrocyte membrane. Thin- section electron microscopy (The Rockefeller University Press, 1980)
A filamentous network underlying the human erythrocyte membranes can be clearly visualized in situ by electron microscopy of thin sections of specimens fixed with tannic acid-glutaraldehyde. The network is composed of two layers: the first, a layer of vertical components with granular appearance, which are seen to be directly associated with the membrane proper, and the second, a horizontally disposed, anastomosing meshwork of filamentous components, approximately 9 nm in thickness, which are attached to the vertical components. The diameter and appearance of the filamentous components are similar to those of purified spectrin. EDTA treatment (0.1 mM, pH 8.0), which was used to extract spectrin and actin, resulted in the disappearance of the filamentous meshwork, leaving only the granular components.